The Relationship Between Social Media Addiction and Medical Students' Self-Esteem - Gustianda, Mochammad Rizka; Isrona, Laila -; Nazar, Julizar; Noer, Mustafa; Sauma, Eldi (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2024)
Background: According to the most recent report, social media users in Indonesia have reached 40% of the country's total population, or about 106 million, based on the 2017 Tetra Pax Index survey. Numerous studies have shown that social media addiction exists in light of the increased usage of social media. Addiction to social media is one of the things that can damage one's self-esteem. Addiction to social media can make someone compare themselves to other people, which lowers their self-esteem.Aims: The purpose of this research is to ascertain how social media addiction and self-esteem relate to Universitas Andalas medical study program students in batches 2019, 2020, and 2021.Case Discussion: This study used a cross-sectional design, employed the Social Media Disorder Scale and Rosenberg Self-Esteem Scale questionnaires, and included 141 respondents in total. The results showed that 24.8% of respondents were classified as social media addicts and 31.9% as having low self-esteem. The rank Spearman's analysis test revealed a significant correlation between social media addiction and self-esteem (r=-0.0168, p=0.024).Conclusion: Due to the constant advancement of new technologies and the significant growth in applications, social media addiction will continue to be a severe problem that can negatively impact a person's self-esteem even though using social media is a common and accepted modern behavior.